Fiscal Reform Over Ten Years of Transition - Tsibouris, George (IMF Working Papers; Working Paper, 2000)
This paper analyzes fiscal reforms in transition economies during the decade leading up to 1998. The paper argues that macroeconomic stabilization, price liberalization and privatization-the core reforms visualized by the shock therapy approach-are necessary but not sufficient conditions for a complete transition to a market economy. Further deep changes-such as the creation of new fiscal institutions, changes in incentives and processes, and changes in the role of government-are needed.